Bioactivities of a-mangostin from Garcinia malaccensis Hk.f - Zohri, Farah Syahidah A; Bakhtiar, M. Taher; Darnis, Deny Susanti; Nakazibwe, Sauba; Solachuddin Jauhari, Arief Ichwan (2010)
Guttiferae family is well known to have a wide range of phytochemical sontituents and bioactivities. A phytochemical investigation of Garcinia malaccensis leasd isolaton of a-mangostin, b-mangostin and a triterpenoid. a-Mangostin, a xanthone has a lot of health benefits. Many studies have been reported to investigate the biological activities of a-mangostin. The present study was carried out to evaluate the antimicrobial, antioxidant and anticancer activities of a-mangostin. Its structural determination was done based on its spectroscopic analysis. a-Mangostin was tested for antimicrobial sensitivity via disc diffusion method against 4 bacteria. Results showed that S.aureus culture formed a clear inhibition zone. The diameter of zone of inhibition observed was 8 mm and minimum inhibition concentration (MBC)value was 0.1mg/mL, indicted that a-mangostin is a bacteriostatic and bactericidal agent which correlates to presence of hydroxyl group in its structure. In antioxidant properties tests, dot-blot DPPH staining showed a positive antioxidant activity of a-mangostin. In FTC method, a-mangosin was proved to be good lipid peroxidation inhibitor, whereas in DPPH free redical scevenging activity method, it has very weak scavening effects on free radicals. In antiproliferative assay, a-mangostin exhibited activity against K562 and showed different activity against HSC3 and H1299 cell lines. Against K562, it exerted the value of IC50 20ug/mL. This study can form a foundation for future studies in investigating of biological activities of-amangostin and developing the natural abundant in improving a healthy community.